IDENTİFİCATİON OF LEİSHMANİA TROPİCA FROM PEDİATRİC VİSCERAL LEİSHMANİASİS İN SOUTHERN MEDITERRANEAN REGION OF TURKEY. - Derya Alabaz; Fadime Eroğlu; Hüseyin Elçi; Ümmühan Çay (Mediterranean Journal of Hematology and Infectious Diseases)
Background;  Protozoa of the genus Leishmania are obligate intracellular parasites and Leishmania species cause a spectrum of species-specific clinical symptoms known as cutaneous, mucocutaneous and visceral leishmaniasis. Leishmania major and Leishmania tropica are known to cause cutaneous leishmaniasis, while Leishmania infantum and Leishmania donovani cause visceral leishmaniasis (VL). However, molecular studies in recent years have shown that Leishmania species cause different clinical symptoms.